Stardust - Gaiman, Neil; Vess, Charles (New York : William Morrow, an imprint of HaperCollins publishers, 2012)
In the quiet English hamlet of Wall, Tristran Thorn embarks on a remarkable journey through the world of Faerie to recover a fallen star for his lover, the hauntingly beautiful Victoria Forester.
Additional edition statement from p.[4] of cover.
"This special edition of 'Stardust' includes a specially commissioned frontispiece and chapter-opening art by Charles Vess, a revised introduction and an all-new postscript by the author, and an early Wall story entitled: 'Wall: a prologue.'"--p.[4] of Cover.
Keywords: Young men -- Fiction; Meteors -- Fiction; Fantasy fiction; Adventure fiction; Romance fiction